Imerslund-Grasbeck syndrome- a rare cause of megaloblastic anemia in an infant with homozygous mutation in CUBN gene: a case report and review of the literature - Agarwal, Mehak; Suresh, Sanmathi; Jayaraman, Dhaarani; Shanmugam, Sri Gayathri (International Journal of Contemporary Pediatrics, 2021)
Megaloblastic anaemia is one of the important causes of pancytopenia in children and nutritional deficiencies of vitamin B12 and folate are the most common causes comprising 95% of these cases. Defects in absorption, transport and metabolism of vitamin B12 are well described, however, are very rare. We report a rare case of Imersland Grasbeck syndrome, in an infant who presented with pancytopenia, with defective absorption of B12-intrinsic factor complex at the ileum and defective tubular reabsorption of proteins in renal tubule due to same protein defect caused by mutations in two genes – CUBN (cubilin) and AMN (amnionless).